BETWEEN FICTION AND HISTORY: THE NARRATIVES OF MAJAPAHIT IN GIGREY'S NOVEL 'MADA' - Ajeng Aisyah Fitria; Ardian Nugraha Priyatama (Leksema: Jurnal Bahasa dan Sastra, 2024)
The Majapahit Empire has been a source of inspiration for writers of historical fiction, such as Gigrey with his novel Mada. Unfortunately, these historical fictions have the possibility to make readers experience misunderstanding in comprehending history. Therefore, this study aimed to reveal to what extent historical deviation can be considered as creativity and not deviation and whether it can be considered a deviation when the writer develops the history excessively. This study employed a descriptive-qualitative method and used Lindbald's theory of historical fiction for analyzing the data. The result shows that there is a historical narrative that can be categorized as creativity because it is so imaginative and does not trap readers in false history. Meanwhile, one form of creative change in the novel that traps can be seen when Nertaja is told as Tribhuwana Wijayatunggadewi's adopted son. Because of these creative changes, many readers are trapped in a false history as evidenced by the comments on Goodreads. This is exacerbated by promotional narratives about the author's extensive research, making common reader even more trapped in the falsehood.